Dampak Peningkatan Karir dan Beban Kerja terhadap Kepuasan Kerja Pegawai Dinas Pendidikan Kota Binjai - Aisyah Fatma Neliza; Aprinawati Aprinawati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the impact of career development and workload on job satisfaction among employees at the Education Office of Binjai City. The study involved 78 respondents, all of whom are employees of the Education Office of Binjai City, selected using a total sampling technique. The research method employed is quantitative with multiple linear regression analysis. Data was collected through questionnaires and analyzed using normality tests, multicollinearity tests, hypothesis tests, and multiple linear regression. The results show that career development has a positive and significant effect on job satisfaction, indicating that career advancement opportunities play an important role in enhancing job satisfaction. Additionally, workload also has a positive and significant effect on job satisfaction, showing that effective workload management can improve employee satisfaction. Overall, both career development and workload have a significant impact on job satisfaction. These findings provide recommendations for the Education Office of Binjai City to continue improving policies related to career development and workload management to enhance employee job satisfaction, which in turn can support better organizational performance.